Literarna zmožnost kultiviranega bralca in Evropski literarni okvir - Zajc, Ivana (Jezik in slovstvo, 2019)
The article presents the implicit factors that influence the form of literary competence in a particular community and synthesises its basic components. The European Literary Framework (2012) describes the development of this competence in secondary education and proposes literary texts for each stage of its development. The article examines which components of literary competence are included in the framework and how it understands them. It also determines where the framework corresponds with the systemic literary didactic paradigm that determines literature classes in Slovenian grammar schools and develops a cultivated reader, as well as where it deviates from it.
Keywords: Evropski literarni okvir; književnost; kultivirani bralec; literarna zmožnost; sekundarno izobraževanje; sistemska didaktika književnosti